Effect of Soil Stabilizers on the Structural Design of Flexible Pavements - Dhanoa, Navtaj Singh (My University, 2014)
Poor subgrade soil conditions can result in inadequate pavement support and reduce pavement life. Soils may be improved through the addition of chemical or cementitious additives. These chemical additives range from waste products to manufactured materials and include lime, Class C fly ash, Portland cement, cement kiln dust, RBI Grade 81. These additives can be used with a variety of soils to help improve their native engineering properties. The effectiveness of these additives depends on the soil treated and the amount of additive used. Design of the various pavement layers is very much dependent on the strength of the subgrade soil over which they are going to be laid. The subgrade strength is mostly expressed in terms of California Bearing Ratio (CBR). Weaker subgrade essentially requires thicker layers whereas stronger subgrade goes well with thinner pavement layers. The pavement and the subgrade mutually must sustain the traffic volume. The Indian Road Congress (IRC) encodes the exact design strategies of the pavement layers based upon the subgrade strength which is primarily dependant on CBR value for a laboratory or field sample soaked for four days. For an engineer, it’s important to understand the change of subgrade strength. This project is an attempt to understand the strength of subgrade in terms of CBR values subjected to different types of stabilizers. Treatment with cement and lime was found to be an effective option for improvement of soil properties, based on the testing conducted as a part of this work. It was found that with the addition of stabilizers i.e. cement and lime, the C.B.R. increased up to a certain limit but after that the C.B.R. decreased even on the further addition of stabilizers.
ME, CED
Keywords: Soil; Stabilizers; Flexible; Pavements; CBR; MDD